Práticas de leitura por meio de oficinas literárias no ensino médio - Muniz, Aline de Assis Rodrigues do Amaral (2020)
This research was motivated by professional experience as a teacher of Portuguese Language and Literature in Basic Education, in particular, with regard to the practice of reading literature at school. Based on this motivation, the main objective of this work aims to contribute to the area of Letters in order to seek some possibilities for the teacher to act as a mediator, leading his students to become competent in literary reading. The theoretical foundation is based, mainly, on the ideas of Antonio Candido (1972; 1988) about the value of literature for the human formation of the individual, as well as Rildo Cosson (2012) regarding the need for literary literacy for the formation of the reader. Literary workshops in high school were proposed and carried out through field research. The results obtained allow us to point out that literary workshops are an effective method of literary literacy, since the activities carried out aroused the involvement and criticality of the participating students.